2018
DOI: 10.1155/2018/3462136
|View full text |Cite
|
Sign up to set email alerts
|

Venom fromBothrops lanceolatus, a Snake Species Native to Martinique, Potently Activates the Complement System

Abstract: Bothrops lanceolatus snake venom causes systemic thrombotic syndrome but also local inflammation involving extensive oedema, pain, and haemorrhage. Systemic thrombotic syndrome may lead to fatal pulmonary embolism and myocardial and cerebral infarction. Here, we investigated the ability of B. lanceolatus venom to activate the Complement system (C) in order to improve the understanding of venom-induced local inflammation. Data presented show that B. lanceolatus venom is able to activate all C-pathways. In human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 58 publications
0
24
0
2
Order By: Relevance
“…Current understanding indicates that snake venoms trigger complement activation in humans (27)(28)(29)(30)(31)(32)(33)(34)(35)(36), but the overall molecular mechanisms induced by the envenomation have remained underexplored. Here, by coupling in vitro and in vivo approaches, we have determined that N. annulifera venom induces reduction in complement pathways activity, anaphylatoxins generation and sTCC assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current understanding indicates that snake venoms trigger complement activation in humans (27)(28)(29)(30)(31)(32)(33)(34)(35)(36), but the overall molecular mechanisms induced by the envenomation have remained underexplored. Here, by coupling in vitro and in vivo approaches, we have determined that N. annulifera venom induces reduction in complement pathways activity, anaphylatoxins generation and sTCC assembly.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, venoms from snakes of different genera, such as Trimeresurus, Bothrops, and Micrurus, have been shown to trigger complement activation in normal human serum (NHS) in vitro, leading to anaphylatoxin generation and soluble Terminal Complement Complex (sTCC) assembly. These events are in part associated with the action of snake venom metalloproteinases (SVMP) and snake venom serine proteinases (SVSP) on central complement components and regulators (27)(28)(29)(30)(31)(32)(33). In addition, other studies have demonstrated depletion of C3 and Factor B (34) and an increase in anaphylatoxins and sTCC plasma levels in envenomated patients, indicating complement activation (35,36).…”
Section: Introductionmentioning
confidence: 99%
“…B. lanceolatus venom can activate all three complement-pathways. In an ex vivo human blood assay, this venom strongly induced the generation of anaphylatoxins, such as C3a, C4a, C5a and the soluble terminal complement complex [211,212]. Venoms from numerous other species from the genus Bothrops are able to activate the complement system by one or several activation pathways, generating high quantities of anaphylatoxins by directly cleaving C3 and C5 or by inactivating the regulator C1-INH.…”
Section: A Tma-type Mechanism?mentioning
confidence: 99%
“…In this regard, activation of the complement cascade by 19 different Bothrops species from South and Central America was demonstrated to occur by one or more pathways through their action either by directly cleaving C3 and C5 factors or by inactivating the soluble C1 inhibitor, C1-INH factor (71, 72). Moreover, activation of the complement system by B. lanceolatus snake venom in human serum has been reported (101).…”
Section: Inflammation Induced By Viper Snake Venommentioning
confidence: 99%